The future of international construction - Bon, Ranko (Thomas Telford, 2000)
Beginning with a brief background and history of international construction, Bon and Crosthwaite discuss the future of the industry and attempt to predict short and medium-term developments.
Keywords: Construction industry -- Forecasting.; elektronické knihy; electronic books